The Age of Entertainment Marketing: The Case of Mercedes and Product Placement in Hollywood Cinema - Martín, Alicia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
We are in the era of “entertainment marketing”, which arises as a union between the consumer and entertainment needs, as technology consumers are no longer conceiving advertising as something flat and promotional. This article focuses on Mercedes' application of product placement advertising techniques in North American cinema, with an aim of transmitting its brand values: quality, luxury, style, and fashion. To obtain the results, quantitative and qualitative research techniques have been used, as well as content analysis following the methodology proposed by Méndiz.